Utilization of roasted male coconut (Cocos nucifera L.) flowers as coffee substitute - Mendoza, Kelvin R.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
The potential of the male coconut flowers as a raw material in the development of a coffee substitute was explored. Optimization of roasting parameters for the male Cocos nucifera L. flowers were studied using response surface methodology. The effects of roasting time and temperature on the moisture content, water activity, L, a, b color values, and consumer acceptability ratings were observed. The interaction of the roasting parameters with the response variables was used to determine response surfaces and to develop respective prediction models. All model equations were found to be significant (p < 0.05) and were used to determine the optimum roasting time-temperature region. The area generated for the optimum region was a five-sided polygon and the five time temperature combinations where the boundaries intersect are the following: 185°C for 10 min, 196°C for 10 min, 190°C for 16 min, 179°C for 26 min, and 170°C for 30 min. Two treatments, one outside (140 °C for 12 min) and another inside the optimum region (180 °C for 18 min), were used to verify the capability of the models to predict the relationship between the variables. The calculated mean from each model equation was compared to the experimental values observed for both treatments. Means were compared using one sample t-test (α= 0.05). Not all experimental means were found to be statistically similar to the means provided by the models, indicating the inadequacy of the models as prediction tools for the relationship of roasting time and temperature to the physicochemical and sensory attributes. The proximate composition of the roasted male coconut flowers, from the 180 °C ? 18 min treatment, was also determined and compared to literature values for the fresh male coconut flowers.
Thesis Classification: C
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Coconut -- Philippines; Coconut -- Processing; Coffee